Leadership, organizational culture, and work culture as determinants of employee performance: The mediating role of organizational commitment in a maritime vocational institution - Tungkup, Doharman Lumban; Rokhman, Fathur; Qudus, Nur; Irwan, Irwan (Edelweiss Applied Science and Technology, 2026)
This study aims to examine the influence of leadership, organizational culture, and work culture on performance through organizational commitment. Research that explores the roles of leadership, organizational culture, and work culture in shaping employee performance within vocational education settings, particularly maritime vocational schools, remains limited and therefore requires further investigation. Vocational institutions possess organizational and work cultures that tend to differ from academic institutions, which represents the novelty of this study. A quantitative causal approach was used to test relationships among variables, and a survey method was applied for data collection. Data were obtained from employees of the Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, involving 141 participants as a saturated sample. Analysis was conducted using Variance-Based Structural Equation Modeling. The findings show that work culture enhances employee performance, although it does not produce a significant effect on organizational commitment. Organizational culture strengthens commitment, which subsequently improves performance. Leadership also contributes to strengthening commitment, yet does not directly influence performance. Organizational commitment increases performance and mediates the relationship between organizational culture and performance, but does not mediate the relationships involving work culture or leadership and performance. The study highlights that improving employee performance is more effectively achieved through a positive and consistent organizational culture, supported by leadership practices that encourage commitment. Organizational commitment emerges as a crucial element in developing psychological attachment that promotes higher performance.